O grupo ciclístico Massa Crítica em Belo Horizonte: relações entre movimentos sociais e lazer - Irene Benevides Dutra Murta (2015)
The present research aimed at understanding possible relationships between social movements and leisure, by conducting a case study of the members of the Critical Mass group from Belo Horizonte. In order to achieve that aim, the experience of those people were studied, as well as the main motivations and interests that lead them to associate with the group. The political actions of the group were also investigated, in order to understand the way in which the members promote a political struggle by proposing changes to the dominant cultural structure regarding the insertion of cycling activity in the urban environment. The way the group is perceived in the city was also evaluated through the participation of non-members who perceived the group, even if as an ephemeral phenomenon. The methods employed for achievement of the described aims were field observation, allied with participation in group meetings. Group discussions and social media interactions - which are the main form of articulation of the group - were followed consistently. As results, the present research indicates that there was no consistent understanding of the group demands on the part of the non-members interviewed, as there was no dialogical interaction. The Critical Mass movement was found not to establish intrinsic relationships with the leisure dimension, which is evidenced in the form of their actions. The will to engage in a political cause that claims the right to the city, the possibility of meeting new people and the search for pleasant moments are identified as the greater motivators for group participation. Thus, the experience of the Critical Mass group meetings are not considered only for their leisure dimension, neither are they restricted to the political dimension, but as the possibility of an entertaining form of political engagement and statement. We believe it possible to overcome the archaic and functionalistic conceptions of leisure as an opposition to work, or simply as a form of occupying free time. We therefore contribute to the area of leisure, by associating it to the social-political dimension, and also to the area of sociology, by looking at social mobilization from a new standpoint. In addition, even if in a less direct way, we aim to contribute to the debate about the right to the city, so problematized in the present.